The interplay between total mercury, methylmercury and dissolved organic matter in fluvial systems: A latitudinal study across Europe. (1st November 2018) - Bravo, Andrea G.; Kothawala, Dolly N.; Attermeyer, Katrin; Tessier, Emmanuel; Bodmer, Pascal; Ledesma, José L.J.; Audet, Joachim; Casas-Ruiz, Joan Pere; Catalán, Núria; Cauvy-Fraunié, Sophie; Colls, Miriam; Deininger, Anne; et al.
Abstract: Large-scale studies are needed to identify the drivers of total mercury (THg) and monomethyl-mercury (MeHg) concentrations in aquatic ecosystems. Studies attempting to link dissolved organic matter (DOM) to levels of THg or MeHg are few and geographically constrained. Additionally, stream and river systems have been understudied as compared to lakes. Hence, the aim of this study was to examine the influence of DOM concentration and composition, morphological descriptors, land uses and water chemistry on THg and MeHg concentrations and the percentage of THg as MeHg (%MeHg) in 29 streams across Europe spanning from 41°N to 64 °N. THg concentrations (0.06–2.78 ng L −1 ) were highest in streams characterized by DOM with a high terrestrial soil signature and low nutrient content. MeHg concentrations (7.8–159 pg L −1 ) varied non-systematically across systems. Relationships between DOM bulk characteristics and THg and MeHg suggest that while soil derived DOM inputs control THg concentrations, autochthonous DOM (aquatically produced) and the availability of electron acceptors for Hg methylating microorganisms (e.g. sulfate) drive %MeHg and potentially MeHg concentration. Overall, these results highlight the large spatial variability in THg and MeHg concentrations at the European scale, and underscore the importance of DOM composition on mercury cycling in fluvial systems. Graphical abstract: Conceptual framework of (a) streams characterized by high inputs of terrestrial DOM and high concentrations of THg and (b) streams enriched in microbial/algal DOM depicting high MeHg formation (%MeHg). Image 1 Highlights: Stream total-Hg and MeHg concentrations across European latitudinal gradient highly variable. Soil derived organic matter inputs control total-Hg in European streams. Autochthonous organic matter controls MeHg formation in European streams.